m ( 2 m + n − m n ) ( m − n ) 2 < x
The smallest value of x which satisfies the inequality above for all pairs of positive integers ( m , n ) such that m > n , can be expressed in the form b a , where a and b are positive coprime integers. What is the value of a + b ?
Details and assumptions
The arithmetic mean of 2 numbers m and n is 2 m + n .
The geometric mean of 2 numbers m and n is m n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good job!
One tricky question: why can't x be smaller than 8 ?
Log in to reply
You can make m n arbitrarily close to 1, by picking a very large n and choosing m = n + 1 .
So while the inequality is strict, the bound is tight
Log in to reply
Yes, this is exactly what is going on. It is also important that as x approaches 1 , the expression 2 ( 1 + x ) 2 approaches 8 .
simplifying given inequality we get
( 1 + m n ) 2 < 2 x . . . . . ( i )
o r , m n < ( 2 x − 1 )
now,m,n are positive integer then their ratio must be rational.but if we take x<8 (x>2,since n is positive) then we get an irrational number on right side,or if we get rational number(like taking x=5) then
m n = 2 1
but if,
m n = 2 1
then we find x > 3 + 2 2
For this discrepancy we can't take x smaller than 8.
Log in to reply
**we find x > 3 + 2 2 from equation (i)
Log in to reply
@Diago Luise – Your inequalities are correct, but the logic after that escapes me.
Wow,I was so much worried that I did correct but my answer came an integer and not a fraction..and finally I was correct..
Given, m ( 2 ( m + n − m n ) ( m − n ) 2 < x
o r , 2 m ( m + n ) 2 < x
[Dividing nominator and denominator on L.H.S by ( m − n ) 2
since, m > n ,
hence, ( m − n ) = 0 ]
o r , ( 1 + m n ) 2 < 2 x . . . . . . . . . . . . ( i )
[Dividing nominator and denominator on L.H.S by m
since,m>n and n is positive integer then m = 0 ]
but, m n < 1 ( s i n c e , m > n )
hence, m n < 1
then, ( 1 + m n ) < 2
o r , ( 1 + m n ) 2 < 4 . . . . . . . . . . . . ( i i )
compairing (i) and (ii) we can say that 2 x = 4
hence,x=8 then a=8,b=1
(a+b)=9 (Ans)
Again, you have to be careful and explain why x cannot be smaller than 8 . Here is an example of a problem, where one can get in trouble without that,
Suppose n and m are arbitrary positive integers, n > m . What is the smallest x such that 8 − m n − n m < x . What is x ?
You see, one would be correct to say that m n > 0 and n m > 0 , so 8 − m n − n m < 8 . However, the correct smallest x is 6 , because the inequality can be improved. There is also an issue, both in this and in the original problem, that m n is a rational number, rather than arbitrary real number.
Make the substitution m = n + k , where k is a positive integer. By multiplying both the numerator and denominators by the sum of the two means and exploiting the difference of squares identity in the denominator, you get the following rational expression in n and k: n + k 2 ( 2 n + k + 2 n 2 + k n ) .
The value of this expression decreases with k and increases with n . Hence, put k = 1 , and evaluate the limit as n → ∞ . The limit is 8 = 1 8 , so the answer is 8 + 1 = 9 .
It is really not obvious that the value decreases with k and increases with n .
m ( 2 m + n − m n ) ( m − n ) 2 = m ( m + n − 2 m n ) 2 ( m − n ) 2 = m ( m − n ) 2 2 ( m − n ) 2 = m 2 ( m + n ) 2 = 2 ( m n + 1 ) 2 ≤ 2 ( n + 1 n + 1 ) 2 (since m > n and they are positive integers) Now, note that n + 1 n < n + 2 n + 1 for positive integers n and lim n → ∞ n + 1 n = 1 . Hence m ( 2 m + n − m n ) ( m − n ) 2 < 2 ( 1 + 1 ) 2 = 8 , which is the smallest value of x . The value of a + b is therefore 8 + 1 = 9 .
Simplifying we get, LHS = 2[1 + 2sqr(n/m) + (n/m)] So, n/m must be a perfect square; Here, given m>n and for large consecutive perfect square n/m is nearly equal to 1. So, least value of x will be 2(1+2+1) = 8. So, a = 8 and b = 1.
Problem Loading...
Note Loading...
Set Loading...
We can write 2 m + n − m n as 2 1 × ( m − n ) 2 . This turns the given expression to 2 m ( m − n ) 2 ( m − n ) 2 which we can then further simplify to m ( m − n ) 2 2 ( m − n ) 2
Now we can write ( m − n ) = ( m − n ) ( m + n ) and subsitute into the resulting expression to get m ( m − n ) 2 2 ( m − n ) 2 ( m + n ) 2 .
This simplifies to m 2 ( m + n ) 2
Writing m = m × m we can further rearrange the expression to give us
2 ( 1 + m n ) 2 .
Since we know that m n < 1 , we know that the entire expression is less than 2 × ( 1 + 1 ) 2 = x = 8